Comparative Effects of Different Energy and Nutrient Contents in a Conventional Very Low Calorie Diet Obesity Treatment - Kuwahara, Hiroshi; Eto, Hiroshi; Ito, Sukenobu; Akiyama, Eiichi; Mieno, Yuko (Eiyōgaku zasshi, 1998)
We modified the usual nutrient composition of a conventional very low calorie diet (VLCD) for treating moderate to severe obesity from 380kcal (40g of protein) to 460kcal (55g of protein) and examined the effects of the difference on the obesity treatment. All the subjects were inpatients of Yufuin Kosei-Nenkin Hospital: 44 had an average age of 46.1±2.5 years (12 males and 32 females) who took 380kcal/day of VLCD; and 39 had an average age of 45.1±2.3 years (12 males and 27 females) who took 460kcal/day of VLCD. After administering 380kcal or 460kcal of VLCD in accordance with our treatment program, the body weight of all subjects significantly decreased after four weeks in both groups the body mass index (BMI) being significantly decreased after two weeks in the 380kcal group and after three weeks in the. 460kcal group. Total cholesterol, LDL-cholesterol and triglyceride were significantly decreased in both groups after four weeks, while HDL-cholesterol was significantly decreased in the 380kcal group, but only slightly decreased in the 460kcal group. The atherogenic index (T-chol. -HDL-chol. /HDL-chol.) showed an apparent improvement in the 460kcal group. The nitrogen balance was significantly improved in the 460kcal group compared with that of the 380kcal group. Serum iron was lowered significantly after four weeks in both groups, but recovered to the normal range when both groups returned to a 1, 200kcal diet. The decrease in weight after four weeks was not significantly different between the two groups; however, the 460kcal group had more favorable results for serum lipid, atherogenic index, and nitrogen balance. In conclusion, 460kcal a day seems to have been more suitable than 380kcal a day for the VLCD therapy.